2010
DOI: 10.1167/10.10.16
|View full text |Cite
|
Sign up to set email alerts
|

Precueing attention to the target location diminishes crowding and reduces the critical distance

Abstract: The identification of a peripheral target surrounded by flankers is often harder than the identification of an identical isolated target. This study examined whether this crowding phenomenon, and particularly its spatial extent, is affected by the allocation of spatial attention to the target location. We measured orientation identification of a rotated T with and without flankers. The distance between the target and the flankers and their eccentricity varied systematically. We manipulated attention via periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
188
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(221 citation statements)
references
References 59 publications
25
188
2
1
Order By: Relevance
“…The beneficial effect of extra-large letter spacing might also be linked to sluggish visuospatial attention in dyslexic children (7,36). Indeed, spatial attention diminishes crowding by improving accuracy of target identification or reducing the critical spacing (21,37). Sluggish spatial attention has recently been observed even in at-risk prereaders who later became dyslexic (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of extra-large letter spacing might also be linked to sluggish visuospatial attention in dyslexic children (7,36). Indeed, spatial attention diminishes crowding by improving accuracy of target identification or reducing the critical spacing (21,37). Sluggish spatial attention has recently been observed even in at-risk prereaders who later became dyslexic (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Because the eccentricity of our targets was 6°visual angle, our closest edge-to-edge distance between stimuli of 4°is unlikely to have produced significant crowding. Yeshurun and Rashal (2010) showed that spatial attention further reduces the target-flanker distance at which the flankers no longer interfere with the target identification. Second, Pelli, Palomares & Majaj (2004) have reported that crowding affects feature detection, which was not necessary to solve our task.…”
Section: Discussionmentioning
confidence: 99%
“…One proposed mechanism for maintaining stability is predictive remapping of neurons' visual fields just before the eyes actually start to move (for review, see Melcher, 2011). With predictive remapping, the receptive field of some neurons shifts toward the location they will occupy after the eye movement (Duhamel et al, 1992). It is hypothesized that predictive remapping is driven by an efference copy of the motor command that is sent back to the oculomotor cortex, informing the brain about the upcoming eye movement.…”
mentioning
confidence: 99%
“…A study by Harrison et al (2013) investigated whether predictive remapping causes peripheral targets to be released from crowding just before an eye movement is made. In the first experiment, participants were asked to report the orientation of a small, peripherally-presented stimulus that was crowded by four vertically oriented stimuli (flankers).…”
mentioning
confidence: 99%